Pemberdayaan Kelompok PKK Melalui Pelatihan Pembuatan Batik Jumputan dan Digital Marketing di Kelurahan Kepanjenlor Kota Blitar - Afika Qothrunnada; Nurjanti Takarini (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Jumputan batik is batik which is done using tie dyeing, tied with rope, dyed using powdered textile dyes. This batik does not use wax, but the cloth is sewn and tied using rubber or rope. The socialization was carried out to PKK RT 04 RW 06. The methods used in this community service were lectures or delivery of material, demonstrations and the practice of making batik. The background of the socialization was to add insight to PKK mothers through training on how to make jumputan batik and digital marketing. The socialization of jumputan batik aims to increase community creativity in entrepreneurship and preserve local culture in the area. Batik making training is expected to support the community's economy in Kepanjenlor Village, Blitar City. The results of this socialization were that PKK mothers became enthusiastic about doing jumputan batik products, were able to market their products through digital marketing, became more skilled at making jumputan batik, and were able to develop potential in independent entrepreneurship through batik training.